Job Satisfaction and Workplace Flexibility Models in Reducing Job Hopping Among Generation Z in an Agriculture Company in Karawang Regency - Eti Rusmiati; Endaryanto Endaryanto; Didin Hikmah Perkasa (Dinasti International Journal of Education Management And Social Science, 2025)
This study examines the relationship between job satisfaction, work flexibility and job hopping tendencies among Generation Z employees. By exploring key factors influencing job retention, this research aims to provide insights for employers to develop workplace policies that align with Gen Z’s expectations, fostering a more stable workforce. The methodology used is a quantitative survey involving 120 respondents from Generation Z who work in an agricultural company in Karawang Regency. Data was collected using a questionnaire designed to measure job satisfaction, work flexibility, job loyalty and job-hopping tendencies. Using PLS - SEM outer model, inner model and hypothesis testing to identify the relationships between these variables. The results indicate that job satisfaction and work flexibility positively influence job loyalty.  While flexibility can enhance loyalty, it also encourages job exploration. Job hopping remains common duet o attractive culture, career growth, and better pay. Thus, loyalty alone can’t prevent turnover, as Gen Z’s choices are driven by both personal and professional goals. This study explores Generation Z behavior at workplace by identifying job loyalty as mediator between job satisfaction, flexibility, and job hopping. It also addresses a gap by examining the often-overlooed agricultural sector, where workforce stability is crucial.